Metabolomics Profiling and AKR Characterization During Paurometabolous Development of Corythucha ciliata (Hemiptera: Tingidae). Issue 6 (9th December 2019) - Li, Du; Dewer, Youssef; Qu, Cheng; Li, Fengqi; Luo, Chen
Abstract: The sycamore lace bug, Corythucha ciliata (Say) is an invasive pest infesting trees of the genus Platanus . Both adults and nymphs damage the foliage of sycamore trees. Nymphs cannot survive in low temperatures; however, the sycamore lace bug overwinters as adults. In this study, we analyzed the metabolite profiles of this pest to determine significantly regulated metabolites during paurometabolous development from nymphs to adults. The identification of metabolites is essential to convert analytical data into meaningful biological knowledge. A total of 62 metabolites were identified using GC-MS. Among them, 29 different metabolites showed differences in content among nymphs, adult females (AF), and adult males (AM). Five of the 29 metabolites, including caffeic acid, D-glucose, D-mannose, glycerol and aminooxyacetic acid, were significantly increased and nine of them were significantly decreased during the developmental stages from nymph to adult. In addition, we identified three novel aldo-keto reductase (AKR) genes that may play a significant role in the control of glycerol biosynthesis. Moreover, the characteristics and expression levels of these genes were analyzed. This study will provide us with the necessary information to improve our understanding of the changes in metabolites in C. ciliata during paurometabolous development.